(untitled) (The Review of Diabetic Studies, 2025)
The is no proper definition and law in implementing ayurneuro genetics legal framework in the Mental Health Act regulatory -valuation in India. The Indian legal system lacks in addressing the ethical and regulatory deficit in Genre of ayurveda, neuroscience and neurogenetics, to address the mental trauma and stress faced by people in work setting both in national and multinational companies, thus, to address the ethical inefficiency there needs a neuroayur genetics legal framework to prevent health related issues in more earlier stage of metal distress. Our Indian-traditional medicine, Ayurveda-Achara Rasayana, and neurogenetics cognitive detailing describe human conduct, human psychology, ethical practice, and lifestyle practice to enhance the way of living in a more disciplined way with proper guidance and counseling from childhood till death. The role of ayurvedpsychogenetic counsellor and therapist could enhance the thinking and lifestyle of people in distress with catalyst factors such as self-awareness, implicit prejudices, inbuilt capabilities, personal values, and cognitive biases with adopting achara rasayana techniques.